Delayed action does not always require the ventral stream: a study on a patient with visual form agnosia - Hesse, Constanze; Schenk, Thomas (Cortex, 2014)
It has been suggested that while movements directed at visible targets are processed within the dorsal stream, movements executed after delay rely on the visual representations of the ventral stream (Milner & Goodale, 2006). This interpretation is supported by the observation that a patient with ventral stream damage (D.F.) has trouble performing accurate movements after a delay, but performs normally when the target is visible during movement programming. We tested D.F.'s visuomotor performance in a letter-posting task whilst varying the amount of visual feedback available. Additionally, we also varied whether D.F. received tactile feedback at the end of each trial (posting through a letter box vs posting on a screen) and whether environmental cues were available during the delay period (removing the target only vs suppressing vision completely with shutter glasses). We found that in the absence of environmental cues patient D.F. was unaffected by the introduction of delay and performed as accurately as healthy controls. However, when environmental cues and vision of the moving hand were available during and after the delay period, D.F.'s visuomotor performance was impaired. Thus, while healthy controls benefit from the availability of environmental landmarks and/or visual feedback of the moving hand, such cues seem less beneficial to D.F. Taken together our findings suggest that ventral stream damage does not always impact the ability to make delayed movements but compromises the ability to use environmental landmarks and visual feedback efficiently.
EVALuna2:22298